2022
DOI: 10.3389/fpsyg.2022.774165
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Human Resource Professionals Effective? An Exploratory Lesson From Techno-Based Telco Firms of a Developing Country

Abstract: Extant research primarily focuses on the driving factors of human resource (HR) professionals’ effectiveness in Telco firms of Pakistan. That is due to the need for HR professionals to be effective has risen in the 21st century for gaining sustainable competitive advantage. This research paper aims to examine the level of HR professionals’ effectiveness in Telco firms of Pakistan and explores the strategic functions and their elements, owing to which HR professionals can be effective in fulfilling their tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The data collection techniques used in this research included observation and interviews. Previous scholars (Cohen et al, 2000;Gentles et al, 2015) suggested that in 'phenomenology qualitative research', fewer than ten interviews would be enough if researchers intend to follow informants intensely (Fareed et al, 2022). Most research initiatives, whose purpose is to understand shared perceptions and experiences among a homogeneous group, involve six to twelve interviews (Fareed et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collection techniques used in this research included observation and interviews. Previous scholars (Cohen et al, 2000;Gentles et al, 2015) suggested that in 'phenomenology qualitative research', fewer than ten interviews would be enough if researchers intend to follow informants intensely (Fareed et al, 2022). Most research initiatives, whose purpose is to understand shared perceptions and experiences among a homogeneous group, involve six to twelve interviews (Fareed et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Previous scholars (Cohen et al, 2000;Gentles et al, 2015) suggested that in 'phenomenology qualitative research', fewer than ten interviews would be enough if researchers intend to follow informants intensely (Fareed et al, 2022). Most research initiatives, whose purpose is to understand shared perceptions and experiences among a homogeneous group, involve six to twelve interviews (Fareed et al, 2019). In the interview technique, the selection of informants was based on logical considerations; for example, informants who had a broad and in-depth view of the community phenomenon were chosen for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The study used a convenient sampling technique for both quantitative and qualitative data collection. This sampling was useful 'to obtain extensive information quickly and effectively' [43] (p. 5). For recruitment, employees and managers received an email in which they were asked if they were willing to be involved.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…Employee well-being or occupational stress in particular, do not seem to be a priority for Pakistani organizations. In an qualitative study, Fareed et al (2019) interviewed leading HRM professionals from all PKTelcos. Fareed and colleagues asked these HR professionals questions regarding the challenges faced by PKTelcos and what makes HRM professionals effective in answering those challenges.…”
Section: Practical and Contextual Implicationsmentioning
confidence: 99%